PROSES MORFOLOGIS DALAM BAHASA DAYAK TUNJUNG DI KABUPATEN KUTAI BARAT, PROVINSI KALIMANTAN TIMUR - Hadibrata, Halimi (SUAR BETANG, 2017)
The aim of this research is to discover word class and describing the morphological process of word-formation in Dayak Tunjung. This language is spoken by citizen of West Kutai Region, East Kalimantan. This research applies the qualitative method. The data is collected through survey and note-taking technique. The data is analyzed by using the word-paradigm and valency approach. The word-formation paradigm by affixation, reduplication, and composition to discover word derivation as noun, verb, adjective, and adverb. The valency model of word in sentence is applied to discover preposition and conjunction word class. The result shows that the given language has several word classes, namely noun, verb, adjective, adverb, preposition and conjunction